Implications of Climate Change: How Does Increased Water Temperature Influence Biofilm and Water Quality of Chlorinated Drinking Water Distribution Systems? - Calero Preciado, Carolina; Boxall, Joby; Soria-Carrasco, Víctor; Martínez, Soledad; Douterelo, Isabel (Frontiers in Microbiology, 2021)
Temperature variation can promote physico-chemical and microbial changes in the water transported through distribution systems and influence the dynamics of biofilms attached to pipes, thus contributing to the release of pathogens into the bulk drinking water. An experimental real-scale chlorinated DWDS was used to study the effect of increasing temperature from 16 °C to 24 °C on specific pathogens, bacterial-fungal communities (biofilm and water samples) and determine the risk of material accumulation and mobilisation from the pipes into the bulk water. Biofilm was developed for 30 days at both temperatures in the pipe walls, and after this growth phase, a flushing was performed applying 4 gradual steps by increasing the shear stress. The fungal-bacterial community characterised by Illumina MiSeq sequencing, and specific pathogens were studied using qPCR: Mycobacterium spp., Mycobacterium avium complex, Acanthamoeba spp., Pseudomonas aeruginosa, Legionella pneumophilia, and Stenotrophomonas maltophilia. Sequencing data showed that temperature variation significantly modified the structure of biofilm microbial communities from the early stages of biofilm development. Regarding bacteria, Pseudomonas increased its relative abundance in biofilms developed at 24 °C, while fungal communities showed loss of diversity and richness, and the increase in dominance of Fusarium genus. After the mobilisation phase, Pseudomonas continued being the most abundant genus at 24 °C, followed by Sphingobium and Sphingomonas. For biofilm fungal communities after the mobilisation phase, Helotiales incertae sedis and Fusarium were the most abundant taxa. Results from qPCR showed a higher relative abundance of Mycobacterium spp. on day 30 and M. avium complex throughout the growth phase within the biofilms at higher temperatures. The temperature impacts were not only microbial, with physical mobilisation showing higher discolouration response and metals release due to the increased temperature. While material accumulation was accelerated by temperature, it was not preferentially to either stronger or weaker biofilm layers, as turbidity results during the flushing steps showed. This research yields new understanding on microbial challenges that chlorinated DWDS will undergo as global temperature rises, this information is needed in order to protect drinking water quality and safety while traveling through distribution systems.